Pengaruh Kualitas Layanan BPJS Kesehatan terhadap Tingkat Kepuasan Pengguna Layanan Kesehatan Khususnya pada Pelayanan Rujukan di Kota Medan - Pakpahan, Iyusarah; Rossevelt, Franklin Asido; Aisyah, Dara; Azzahra, Syahirah; Munthe, Jane Bortana Br; Sitompul, Graciela Ulina; Prayoga, Muhammad Alvin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Referral services under BPJS Health in Medan City continue to encounter issues such as delays, mismatched facilities, and limited empathy from healthcare personnel, contributing to rising public dissatisfaction. This study aims to analyze the influence of BPJS Health service quality on user satisfaction in referral services in Medan City. A quantitative approach was employed through questionnaire distribution to BPJS participants who had accessed referral services, with validity and reliability testing conducted on the instrument. Data were analyzed using correlation tests and simple and multiple linear regressions to determine the relationships and effects among variables. The results show that both service quality and referral process quality have strong and significant impacts on user satisfaction. Responsive service, clear procedures, timeliness, and effective coordination between healthcare facilities were found to enhance participants’ perceptions of service quality. The study concludes that improving service quality particularly within referral mechanisms is essential for increasing user satisfaction and improving the effectiveness of healthcare delivery in Medan City.